Karakteristik Fisik dan Uji Aktivitas Antiokidan dengan Metode DPPH Sediaan Sheet Mask Ekstrak Biji Kakao - Meirista, Indri; As'adi, M. Henityo Agung; Putri, Dzakiah Adillah (Universitas Baiturrahim, 2025)
Healthy skin can reflect a person's health. Healthy, clean and bright skin is everyone's dream, especially for women. Antioxidants protect the body from damage caused by free radicals. Free radicals can cause cell damage such as skin wrinkles, dark spots, and dullness. Cocoa beans (Theobroma Cacao Linn) contain catechins, epicatechins, and proanthocyanidins which have antioxidant properties. This study aims to determine how the physical characteristics of cocoa bean extract (Theobroma Cacao Linn) sheet mask and how the antioxidant activity of cocoa bean extract (Theobroma Cacao Linn) sheet mask preparations are produced. This research method is experimental, the data is processed statistically using microsoft excel diagram and visualized in the form of bar graphs. Extraction using percolation method using 96% ethanol solvent then the extract was identified with phytochemical screening test. Formulations were made with different concentrations of active substances and physical properties were carried out including organoleptic test, homogeneity test, viscosity test, pH test, stability test, moisture effectiveness test, irritation test, liking test, and antioxidant test of sheet mask preparations. The results of this study in each evaluation test showed that cocoa bean extract (Theobroma Cacao Linn) sheet mask preparations can be formulated as strong category antioxidant sheet mask preparations with IC50 values in formula 1 of 78.12 µg/ml, formula 2 of 67.08 µg/ml, and formula 3 of 55.2 µg/ml. The physical characteristics of cocoa bean extract (Theobroma Cacao Linn) sheet mask formula 0, formula 1, formula 2, and formula 3 sheet mask preparations can be said to be suitable for use on the face because they pass all tests and fall into the range that has been set.